Rewritable Triple-Mode Light-Emitting Display - Seokyeong Lee; Jong Woong Park; Jihye Jang; Jin Woo Oh; Gwanho Kim; Jioh Yoo; Jong Gun Jung; Hyowon Han; Wei Jiang; Chang Eun Lee; Jungwon Yoon; Kaiying Zhao; et al. (Nano-Micro Letters)
Highlights A rewritable triple-mode light-emitting display (RE-TriLED) was fabricated, enabled by stimuli-interactive fluorescence (FL), room-temperature phosphorescence (RTP), and electroluminescence (EL). Mode-selective multiple light emission is achieved, in which the three emission modes of FL, RTP, and EL are readily manipulated through the controlled evaporation of polar liquids and water. A high-security, full-color information encryption display is demonstrated, wherein optical information encoded in one mode is decipherable only when properly aligned with the other two modes.